Exosomes Derived From miR-212-5p Overexpressed Human Synovial Mesenchymal Stem Cells Suppress Chondrocyte Degeneration and Inflammation by Targeting ELF3 - Zheng, Tianlei; Li, Yan; Zhang, Xiaozai; Xu, Jia; Luo, Ming (Frontiers in Bioengineering and Biotechnology, 2022)
Excessive chondrocyte degeneration and inflammation are the pathological features of osteoarthritis (OA), and altered miR-212-5p may contribute to meniscus and cartilage degeneration. Whether exosomes derived from miR-212-5p overexpressed synovial mesenchymal stem cells (SMSC-212-5p-Exos) could be utilized to treat degenerative chondrocytes is investigated in this study. Down-regulated miR-212-5p and up-regulated E74 Like ETS Transcription Factor 3 (ELF3) expression were detected in OA synovial tissues, which showed a negative correlation (r=-0.55, P=0.002). miR-212-5p directly targeted ELF3 and regulated the relative expression of ELF3 in SMSCs as indicated by luciferase reporter assay and RT-PCR. The relative expression of ELF3, chondrocyte degeneration-related molecules, matrix metalloproteinase, and inflammatory molecules were detected in chondrocytes stimulated with interleukin (IL)-1β or co-incubated with SMSC-212-5p-Exos or SMSCs-derived exosomes (SMSC-Exos). IL-1β induced up-regulation of ELF3, down-regulation of degeneration molecules (Collagen II, Aggrecan, and Sox9), up-regulation of matrix metalloproteinase (MMP-1, MMP-3, and MMP-13), and up-regulation of inflammatory molecules (IL-6, MCP-1, TNF-α, COX-2, and iNOS) could be inhibited by SMSC-212-5p-Exos or SMSC-Exos administration. When compared with the SMSC-Exos, SMSC-212-5p-Exos showed more treatment benefits. All of these indicate that SMSC-212-5p-Exos could suppress chondrocyte degeneration and inflammation by targeting ELF3, which can be considered as a disease-modifying strategy.